The Endogenous GRP78 Interactome in Human Head and Neck Cancers: A Deterministic Role of Cell Surface GRP78 in Cancer Stemness - Chen, Hsin-Ying (Sci Rep, 2018)
Cell surface glucose regulated protein 78 (GRP78), an endoplasmic reticulum (ER) chaperone, was suggested to be a cancer stem cell marker, but the influence of this molecule on cancer stemness is poorly characterized. In this study, we developed a mass spectrometry platform to detect the endogenous interactome of GRP78 and investigated its role in cancer stemness. The interactome results showed that cell surface GRP78 associates with multiple molecules. The influence of cell population heterogeneity of head and neck cancer cell lines (OECM1, FaDu, and BM2) according to the cell surface expression levels of GRP78 and the GRP78 interactome protein, Progranulin, was investigated. The four sorted cell groups exhibited distinct cell cycle distributions, asymmetric/symmetric cell divisions, and different relative expression levels of stemness markers. Our results demonstrate that cell surface GRP78 promotes cancer stemness, whereas drives cells toward a non-stemlike phenotype when it chaperones Progranulin. We conclude that cell surface GRP78 is a chaperone exerting a deterministic influence on cancer stemness.